Ultrafast printing of continuous fiber‐reinforced thermoplastic composites with ultrahigh mechanical performance by ultrasonic‐assisted laminated object manufacturing. Issue 11 (7th August 2020) - Chang, Baoning; Parandoush, Pedram; Li, Xuemu; Ruan, Shilun; Shen, Changyu; Behnagh, Reza Abdi; Liu, Yuan; Lin, Dong
Abstract: Additive manufacturing (AM) of continuous fiber‐reinforced thermoplastic composites (CFRTPCs) has drawn increasing interest and great attention in academic and industrial communities due to its capability of manufacturing complex lightweight structures with high strength at a low cost. In this study, we proposed a novel AM technique to fabricate CFRTPCs using carbon fiber prepreg sheets based on a novel method: ultrasonic‐assisted laminated object manufacturing (UA‐LOM). The prepreg sheets were first cut into 2D shapes, then every eight layers of the sheets were successively consolidated by an ultrasonic‐vibration roller to fabricate one 3D composite part at a faster speed than conventional AM processes where materials are deposited layer by layer. Samples with controlled fiber alignments were prepared for mechanical tests. The post‐processing hot press was carried out to further improve mechanical properties of the additively manufactured components. Results showed that the unidirectional composite samples displayed an ultra‐high tensile strength of 1760.2 (±71.7) MPa and a tensile modulus of 105.7 (±7.2) GPa. The proposed method exhibited superior mechanical performance compared to state‐of‐the‐art AM techniques. The hot‐press‐treated AM composite parts in this work approached the benchmark mechanical properties provided by the prepreg manufacturing company using traditional fabrication methods. Overall, the proposed AM methods of CFRTPCs show great potential applications in aerospace and transportation industries. Abstract : Schematic illustration of the ultrasonic vibration‐assisted laminated object manufacturing method and the properties of printed continuous fiber reinforced thermoplastic composites.